Security and ethics in sustainable e-learning and gamification framework for higher education - Sofiadin, Aidrina (2021)
The world is moving towards achieving sustainable development goals that benefit the environment, society, and the economy. The COVID-19 pandemic has forced many education institutions to shift from traditional learning to online learning. Since 1960, e-learning has been delivering through the website. However, there is a rise in e-learning security and ethical issues that lead to poor education quality and an unsustainable e-learning system. Thus, security and ethics components need to be integrated into a sustainable e-learning and gamification framework. Interestingly, e-learning needs to integrate the gamification context to increase online learning quality and secure learners' education while promoting lifelong learning. To identify the relationship between security and ethics in gamified e-learning, this paper examined and assessed various types of security threads and learners’ ethics and well-being in the e-learning environment. The framework intends to increase e-learning strength in promoting a better e-learning environment, well-being, and lifelong learning among their learners. Thus, enabling sustainable education through a reliable e-learning system.